Recent advances in digital backward propagation algorithm for coherent transmission systems with higher order modulation formats - Schmauß, Bernhard; Asif, Rameez; Lin, Chien-Yu (SPIE 8284, 82840O, 2012)
Recent numerical and experimental studies have shown that coherent transmission with advanced modulation formats i.e. DP-QPSK and QAM are the promising candidates for next-generation systems with data rates of 100Gbit/s and above. Coherent detection is considered efficient along with digital signal processing (DSP) to compensate many linear effects in fiber propagation i.e. chromatic dispersion (CD) and polarization-mode dispersion (PMD). Despite of fiber non-linearities (NL), which are the major limiting factors, next-generation optical systems are employing higher order modulation formats in order to fulfil the ever increasing demand of capacity requirements. However, the channel capacity is limited at higher signal input powers because the system is operating in the non-linear regime. Due to this phenomenon the compensation of non-linearities is a topic of great interest and research these days, especially for long-haul fiber transmission. Digital backward propagation (DBP) algorithm has emerged as a promising and potentially capable candidate, which can jointly compensate fiber dispersion and non-linearities along with the coherent receiver. In this paper we give a detailed overview on the advancements in DBP algorithm based on different types of mathematical models i.e. Wiener (Asymmetric Method) and Wiener Hammerstein models (Symmetric Method). We also discuss the importance of optimized step-size selection, i.e. constant step-size and logarithmic step-size based split step Fourier methods, for simplified and computationally efficient implementation of DBP algorithm. Moreover, by means of numerical investigations we refer to recent system investigations to further improve the performance of DBP algorithm.
lhft_intern.bib::Schmauss2012